Philosophical Review of Materialism and Idealism Limits of Wedding Age in Indonesia; Study of Article 7 Paragraph (1) of Law 16 of 2019 jo. Law 1 of 1974 concerning Marriage - Imam Tabroni; Hisam Ahyani; Dian Permana (Muttaqien, 2021)
This research departs from a juridical confusion regarding the ideal of a person going to get married, where the age of marriage with other provisions regarding age, namely, in terms of philosophical Materialism and Idealism of Marriage Age in Indonesia. Whereas in Indonesian Law on Marriage Marriage is only permitted if men and women have reached the age of 19 (nineteen) years. The purpose of this study is to find out the philosophical review of materialism and idealism of marriage age in Indonesia, with the article 7 paragraph (1) for 16 of 2019 jo. u 1 year 1974 regarding marriage). The conclusion of this research is the philosophical value of materialism and idealism of marriage age is the concept of historical materialism of humans who will choose their readiness in facing marriage, this is because one's age is not a reference, which is the basis for people to get married including their readiness to face material livelihood, readiness self and material. Likewise in Indonesia, the ideal age in society in Indonesia if it is associated with Karl Mark's theory, then the readiness of oneself in the material (economic elements) is as a reference for people to get married.